STUDI LITERATUR: UJI KELAYAKAN MEDIA PEMBELAJARAN E-KOMIK BERBASIS STEM PADA MATA PELAJARAN IPA SMP - Suci Nafiatus Sadea; Sri Wahyuni; Rayendra Wahyu Bachtiar; Aushofil Karimah; Firdha Yusmar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Science subjects, especially environmental materials, are conceptual and abstract, so they often cause difficulties for students in understanding them. One of the learning media reviewed in this literature study is STEM-based e-comics which are developed to improve conceptual understanding in a more interesting and contextual way. The implementation of this media is expected to increase students' interest, involvement, and critical and creative thinking skills in linking science concepts with real problems in the surrounding environment. The selection of STEM-based e-comics learning media is considered an innovative effort to create more effective, flexible, and 21st-century learning. This study uses a literature review method by analyzing nine national articles published in the last five years that focus on the development and implementation of STEM-based e-comics in science learning. The results of the study indicate that STEM-based e-comics have a positive effect on improving conceptual understanding, learning involvement, collaboration skills, creative thinking, and students' problem-solving abilities in accordance with the objectives of the current curriculum.